2012
DOI: 10.1088/0957-4484/23/31/315703
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence model of sulfur passivated p-InP nanowires

Abstract: The effect of ammonium polysulfide solution, (NH₄)₂S(x), on the surface passivation of p-doped InP nanowires (NWs) was investigated by micro-photoluminescence. An improvement in photoluminescence (PL) intensity from individual NWs upon passivation was used to optimize the passivation procedure using different solvents, sulfur concentrations and durations of passivation. The optimized passivation procedure gave an average of 24 times improvement in peak PL intensity. A numerical model is presented to explain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 31 publications
4
29
0
5
Order By: Relevance
“…In contrast, AlInAs/InP heterostructures are expected to be type II, resulting in spatial separation of electrons and holes. The peak near 843 nm in Figure 4 is consistent with the expected wurtzite bandgap of the InP barrier layers [4]. The samples all show a broad peak at higher wavelength, which is attributed to the InAsP QDs.…”
Section: Resultssupporting
confidence: 76%
“…In contrast, AlInAs/InP heterostructures are expected to be type II, resulting in spatial separation of electrons and holes. The peak near 843 nm in Figure 4 is consistent with the expected wurtzite bandgap of the InP barrier layers [4]. The samples all show a broad peak at higher wavelength, which is attributed to the InAsP QDs.…”
Section: Resultssupporting
confidence: 76%
“…Аналогично случаю объемных матери-алов, их наличие может приводить к пинингу уровня Ферми [1,2], что может отрицательно сказываться на работе приборов на основе ННК вследствие их неболь-ших диаметров, соотносящихся с шириной создаваемых приповерхностных обедненных слоев. Для решения этой проблемы, как и в случае объемных полупроводников, особое внимание уделяется различным способам пасси-вации поверхности [3][4][5][6].…”
Section: Introductionunclassified
“…However, the device performance can be remarkably improved by using surface passivation with dielectric materials. Several materials have been reported for the surface passivation of III-V semiconductors including SiO 2 , SiN x and sulfide [13][14][15]. Hashizume et al demonstrated that SiN x passivation can reduce GaN surface band bending [16] and decrease the charged surface state density.…”
Section: Introductionmentioning
confidence: 99%
“…Hashizume et al demonstrated that SiN x passivation can reduce GaN surface band bending [16] and decrease the charged surface state density. The sulfur surface passivation technique was reported for the effective removal of surface states and recovering the band-edge emission of InAs nanowires [15]. It can also lead to the reduction in surface trap density and surface recombination velocity of InP nanowires, resulting in the enhanced photoluminescence emission [15,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation